(untitled) (Public Sector Economics - submission site, 2021)
The purpose of this study is to assess the impact of excise duties on tobacco products on state’s revenues. Increasing excise duties on tobacco may act as a means to reduce the consumption of this product and thus to have a positive effect on citizens’ health and prosperity. Our research showed that an increase in consumer income will result in a certain increase in cigarette consumption and an analogous decrease in fine-cut tobacco consumption, while a similar increase in cigarette price results in a small decrease in cigarette consumption and a very large increase in fine-cut tobacco consumption. Additionally, stepping up an anti-smoking campaign results in a decrease in cigarette consumption. Specifically for Greece we found that during 2019 and 2020 there will be a decrease in the state’s revenues from excise duties on tobacco products of €150-€200 million each year